Exposure to paints and respiratory health ailments among painting workers. Issue 1 (31st December 2023) - Pandey, Padmini; Kiran, U.V
Abstract: Over time, paint chemistry has changed, posing health hazards to house painters. Surveys and interviews scheduled on work profiles determined the exposure to solvents in commercial painting. This research paper aims to identify the respiratory and lungs issues among painters due to their occupation. With this aim, this also explore the worker's experiences with various types of paints regarding health implications. The current study is related to research on the health issues of paint workers. Subjects for the study were chosen by the use of cluster sampling from several places in three districts of Uttar Pradesh, India. An interview schedule was developed to collect relevant and maximum information. The study used a sample size of 150 that was not pre-determined. All the respondents were from the labour class and worked with paints. A schedule of the interview was developed to gather information about the painters' demographic profile and current respiratory health status. Statistical approaches such as Standard Deviation, ANOVA and Pearson's correlation were used for analysis. The study revealed that painters are exposed to paints and face various health issues. Majority of the respondents (50.7%) belongs to lower economic status, followed by upper lower (33.3%), and only 4% of them belong to the upper class. We found a significant difference between the respondent's age and respiratory health. This data indicates that respondents who faced high respiratory issues belong to the age group of 61–75 years, and minimum problems were observed in the age group of 19–32 years. This data shows highly significant differences between age groups, and the problem occurs with the respiratory system in painters. The result indicates that wearing the mask was significantly associated with respiratory problems like cough (p = .004), chest tightness (p = .009), and whistling sound from the chest (p = .000). A perfect positive significant correlation between working year, days, and duration with different lung problems were identified. A perfect positive association (0.443**) was also identified between years of work and cough difficulties, indicating that workers who have worked for prolonged periods were more susceptible to cough. Cough problems were highly associated with painters who worked more days per week. Cough issues were perfectly and significantly associated (0.232**) with painters who use masks while working. The chest sound or whistling gets more intense as the cough problem worsens. Moreover, there was a positive and significant association between discomfort during breathing and working years (.340**), working days in a week (.195*), and working duration (.594**). This study highlighted the risk and problems among painters due to pain, including breathing problems, prolonged cough, chest discomfort, and almost all lung problems.